2002
DOI: 10.1080/03091900210146950
|View full text |Cite
|
Sign up to set email alerts
|

Continuous amperometric monitoring of subcutaneous oxygen in rabbit by telemetry

Abstract: The primary objective was to develop a telemetric oxygen sensor designed for implantation in subcutaneous tissue. In the sensor, the platinum indicating electrode was covered with polythene to retard oxygen entry and avoid interference. Given the potential for large indicating electrodes to deplete oxygen in vivo, some sensors were made with very small indicating electrodes. Sensors were tested in the anesthetized rabbit at various oxygen concentrations. Animals were studied 1 and 5 days after implementation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…A carbon paste electrode was used with differential pulse amperometry to measure changes in current as a correlate of changes in brain PtO 2 in a range of conditions (Lowry et al, 1996; Lowry et al, 1997; Lowry and Fillenz, 2001). An amperometric electrode with a self contained power source has been implanted subcutaneously in rabbits and PO 2 monitored up to 5 days post implant (Ward et al, 2002). Constant potential amperometry has been used with an implanted silver electrode connected to a carbon microsensor and a telemetry circuit (Bazzu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A carbon paste electrode was used with differential pulse amperometry to measure changes in current as a correlate of changes in brain PtO 2 in a range of conditions (Lowry et al, 1996; Lowry et al, 1997; Lowry and Fillenz, 2001). An amperometric electrode with a self contained power source has been implanted subcutaneously in rabbits and PO 2 monitored up to 5 days post implant (Ward et al, 2002). Constant potential amperometry has been used with an implanted silver electrode connected to a carbon microsensor and a telemetry circuit (Bazzu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Clark suggested that 1-3 weeks was required before current stabilized in electrodes implanted in brain (Clark et al, 1958). Some have shown that 24 hrs is sufficient time post implantation of an oxygen sensor to reach a stable, reproducible value for PtO 2 (Liu et al, 1995; Lowry et al, 1997; Ward et al, 2002). A study measuring PtO 2 in brain over 8 days found no significant difference between days, but did not report the error of the measurements (Bazzu et al, 2009) or the time of first measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic islets, particularly porcine islets, are very dependent on oxygen (Ohta et al 1980;Dionne 1989;Hyder et al 1998;Guyton 1991;Soini and Takala 1991;Ward et al 2002;Klossner et al 1974) with an oxygen consumption rate in vitro of 2.5-3 nmol/min per 100 islets and increasing in response to elevated glucose levels (Dionne 1989;Hyder et al 1998;Guyton 1991). Insulin secretion decreases significantly when pO 2 falls below 60 mmHg (Soini and Takala 1991;Ward et al 2002;Klossner et al 1974). The process of islet isolation, culture, and subsequent transplantation results in hypoxia and an immediate loss of islet tissue (Ohta et al 1980;Davalli et al 1996).…”
Section: A Competitive Analysis Of Immunoisolatory Encapsulation Techmentioning
confidence: 97%
“…The amount of oxygen would depend upon passive diffusion within the implantation site with the partial pressure of oxygen (pO 2 )~95 mmHg in arterial blood,~40 mmHg in venous blood, and ranges from 35 to 60 mmHg in the peritoneum and subcutaneous tissues (Carlsson et al 1998;Zacharovova et al 2005;Sweet and Gilbert 2006;Hellerstrom 1967). Pancreatic islets, particularly porcine islets, are very dependent on oxygen (Ohta et al 1980;Dionne 1989;Hyder et al 1998;Guyton 1991;Soini and Takala 1991;Ward et al 2002;Klossner et al 1974) with an oxygen consumption rate in vitro of 2.5-3 nmol/min per 100 islets and increasing in response to elevated glucose levels (Dionne 1989;Hyder et al 1998;Guyton 1991). Insulin secretion decreases significantly when pO 2 falls below 60 mmHg (Soini and Takala 1991;Ward et al 2002;Klossner et al 1974).…”
Section: A Competitive Analysis Of Immunoisolatory Encapsulation Techmentioning
confidence: 97%
“…A wide variety of sensors have been used for direct monitoring of O 2 with the majority of measurements obtained using constant potential amperometry (CPA) at noble metal microelectrodes such gold (Cooper, 1963;El-Deab and Ohsaka, 2003;Holmström et al, 1998) or platinum (Clark et al, 1958;Hitchman, 1978;Travis and Clark, 1965;Ward et al, 2002). The use of carbon-based electrodes has been reported by several groups (Bazzu et al, 2009;Bolger and Lowry, 2005;Lowry and O'Neill, 1996;Venton et al, 2003) and they are often the electrode of choice because of their in-vivo stability and minimal surface poisoning (Bolger and Lowry, 2005).…”
Section: Live Oxygen Sensorsmentioning
confidence: 99%